"What I did last summer" [internship]. - Kariya, S.
Internships offer engineering students a unique window into the real-world workplace and can help students make better career decisions. In the current employment landscape, that on-the-job experience can also prove invaluable. The National Association for Colleges and Employers (NACE, Bethlehem, Pa.) reports a 36.4 percent drop in hiring of recent college grads, who in many cases are competing for fewer openings with more experienced unemployed workers. But doing real engineering as interns can make all the difference when prospective employers are sifting through endless resumes in search of qualified candidates. This article briefly discusses the issues to consider when looking for an internship
Keywords: National Association for Colleges and Employers; Career decisions; Internship; On-the-job experience; Real-world workplace; Students